NUBPL mutations in patients with complex I deficiency and a distinct MRI pattern - Kevelam, Sietske H. (Lippincott Williams & Wilkins, 2013)
OBJECTIVE: To identify the mutated gene in a group of patients with an unclassified heritable white matter disorder sharing the same, distinct MRI pattern. METHODS: We used MRI pattern recognition analysis to select a group of patients with a similar, characteristic MRI pattern. We performed whole-exome sequencing to identify the mutated gene. We examined patients' fibroblasts for biochemical consequences of the mutant protein. RESULTS: We identified 6 patients from 5 unrelated families with a similar MRI pattern showing predominant abnormalities of the cerebellar cortex, deep cerebral white matter, and corpus callosum. The 4 tested patients had a respiratory chain complex І deficiency. Exome sequencing revealed mutations in NUBPL, encoding an iron-sulfur cluster assembly factor for complex І, in all patients. Upon identification of the mutated gene, we analyzed the MRI of a previously published case with NUBPL mutations and found exactly the same pattern. A strongly decreased amount of NUBPL protein and fully assembled complex I was found in patients' fibroblasts. Analysis of the effect of mutated NUBPL on the assembly of the peripheral arm of complex I indicated that NUBPL is involved in assembly of iron-sulfur clusters early in the complex I assembly pathway. CONCLUSION: Our data show that NUBPL mutations are associated with a unique, consistent, and recognizable MRI pattern, which facilitates fast diagnosis and obviates the need for other tests, including assessment of mitochondrial complex activities in muscle or fibroblasts.